2020
DOI: 10.12806/v19/i3/a1
|View full text |Cite
|
Sign up to set email alerts
|

LEADING BY EAR: Podcasting as an Educational Leadership Tool

Abstract: This innovative practice paper explains how a student-produced podcast is used as an educational tool to showcase leadership and ethics. It illustrates how podcasting provides a unique pedagogical experience for students to engage with leadership themes in a way that is accessible, practical, and relevant. In this example, the podcast episodes become an innovative teaching resource, while the creation of it provides an experiential learning opportunity for the student hosts. In creating the work, students deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Such verbal processing of concepts also assisted with their overall understanding of the course material and leadership development (Cases A and C). These findings connect with what Norsworthy and Herndon (2020) explained from a similar study on the use of podcasts in leadership education, where "the entire process [of creating podcasts] becomes one of self-reflection and individual development" (p. 65). Giving students the freedom and autonomy to be self-reflective and to voice what they are learning in the present study contributed to their individual leadership identity development.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Such verbal processing of concepts also assisted with their overall understanding of the course material and leadership development (Cases A and C). These findings connect with what Norsworthy and Herndon (2020) explained from a similar study on the use of podcasts in leadership education, where "the entire process [of creating podcasts] becomes one of self-reflection and individual development" (p. 65). Giving students the freedom and autonomy to be self-reflective and to voice what they are learning in the present study contributed to their individual leadership identity development.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Nielsen and colleagues (2018) examined how the use of teacher-generated podcasts in a blended communications course increased students' theoretical understanding of unfamiliar topics at University College of Northern Denmark. Similarly, Norsworthy and Herndon (2020) explored how using student-produced podcasts in a leadership and ethics course provided a successful educational tool to engage with leadership themes. In order to best grasp and 'digest' course concepts, students created their podcasts, then participated in group discussions about the podcast in the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using podcasts students can be inspired to think more deeply on a specific topic (Teckchandani & Obstfeld, 2016). Additionally, Norsworthy and Herndon (2020) discovered that podcasts could be a transformative tool in management education. Researchers have shown that podcasts and podcasting are powerful strong reflective tools for developing engineering students' communication skills (Ballinas-Gonzalez et al, 2020).…”
Section: Podcasts -Learning and Reflection (State Of The Art)mentioning
confidence: 99%
“…For å få dette til, vil det i mange sammenhenger vaere nødvendig å introdusere innovative løsninger (Snow, 2015). Bruk av podkast i skolen representerer en slik pedagogisk innovasjon (Norsworthy & Herndon, 2020).…”
Section: Metodeunclassified